The common good approach in Copanatoyac and Cuauhtamazaco: a methodological reflection - Gabiño, María del Rosario Andrade (Journal of global ethics, 2025)
In this article, we reflect on the methodology that has been adopted in the application of the common good approach in the Indigenous communities of Copanatoyac and Cuauhtamazaco in Mexico. In doing so, we make repeated reference to Indigenous scholarship on methodological questions. First, we provide an overview of the general criteria that a methodology for research within Indigenous communities should meet. This list comprises the items of positionality, epistemic decolonisation, translation, collaboration, and relationships. In a second step, we connect these considerations with experiences during the data collection. We explore what can be learnt from the corresponding fieldwork to address the challenge of translating between Mexican Spanish and Mexican Indigenous languages. Likewise, we demonstrate that building relationships is crucial to the implementation of such a research project. In this context, successful implementation is not measured by efficiency criteria alone but also includes the value of reciprocity and the question of how communities benefit from the project. Third and last, we draw some conclusions and compile a list of recommendations for follow-up projects. In this list, we incorporate best practises from the present project but also critically highlight weak spots where improvement is still possible.